2012
DOI: 10.1148/radiol.12120424
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Particle Imaging: Visualization of Instruments for Cardiovascular Intervention

Abstract: http://radiology.rsna.org/lookup/suppl/doi:10.1148/radiol.12120424/-/DC1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
98
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(101 citation statements)
references
References 18 publications
(22 reference statements)
0
98
0
Order By: Relevance
“…One key characteristic and fundamental difference of MPI compared with other imaging modalities is the high magnetic moment (about 108 times higher than protons) and the fast relaxivity (about 104 times faster than protons in water) of SPIOs (148,149). In the framework of the Magnetic Particle Imaging Technology consortium, funded by the German Federal Ministry of Education and Research, the University of Lübeck and Philips Technology Innovative Technologies (Hamburg, Germany) created a cooperation initiative to develop this technique (150). MPI depicts the spatial distribution of SPIO particles by using oscillating magnetic fields.…”
Section: Other Selected Applications Of Ferucarbotran and Ferumoxytolmentioning
confidence: 99%
See 1 more Smart Citation
“…One key characteristic and fundamental difference of MPI compared with other imaging modalities is the high magnetic moment (about 108 times higher than protons) and the fast relaxivity (about 104 times faster than protons in water) of SPIOs (148,149). In the framework of the Magnetic Particle Imaging Technology consortium, funded by the German Federal Ministry of Education and Research, the University of Lübeck and Philips Technology Innovative Technologies (Hamburg, Germany) created a cooperation initiative to develop this technique (150). MPI depicts the spatial distribution of SPIO particles by using oscillating magnetic fields.…”
Section: Other Selected Applications Of Ferucarbotran and Ferumoxytolmentioning
confidence: 99%
“…Haegele et al (151,152) reported an approach to visualize a commercially available diagnostic catheter and guide wire for use in MPI guided vascular interventions using a very thin Resovistcoating and a dedicated MPI system. Haegele et al (150) reported that by using MPI, both balloon catheters could be visualized with high temporal resolution and sufficient spatial resolution (Figure 20). Kakite et al (153) evaluated the usefulness of administration of Resovist and MRI for assessing the efficacy of radiofrequency liver ablation.…”
Section: Other Selected Applications Of Ferucarbotran and Ferumoxytolmentioning
confidence: 99%
“…Possible application scenarios for MPI might include cardiovascular imaging and even guidance of cardiovascular interventions. 3,4 In principle, MPI would allow visualization and quantification of vascular pathologies while also being able to determine additional functional parameters in one examination. Further, MPI could be used as an imaging method for percutaneous transluminal coronary angioplasty, if indicated.…”
Section: Introductionmentioning
confidence: 99%
“…4, 6, 15 The idea of integrating a single-sided MPI scanner 16 into a patient table to enable an exact navigation of instruments by the received three-dimensional information is a very promising approach for medical interventions. 17,18 Especially in the proposed interventional scenarios in a catheter laboratory a good patient access and a large FOV are required.…”
Section: Introductionmentioning
confidence: 99%